Studi Fenomenologi: Pengalaman Perawat dalam Menegakkan Diagnosis Keperwatan Berdasarkan Standar Diagnosis Keperawatan Indonesia - Batu, Yuliana; Hasriana, Hasriana; Damayanti, Ana; Lesmana, Hendy; Zulfia, Rahmatuz; Najihah, Najihah (Universitas Malahayati, 2024)
ABSTRACT Diagnosis enforcement is an important aspect of the practice of nursing. Nursing diagnosis have been applied at a number of hospitals and other health facilities, but the knowledge of nurses regarding diagnostic indicators for diagnostic enforcement, and diagnosis enforcement is not difficult. The SDKI as a guideline for the formulation of nursing diagnosis has been implemented since 2017, but in reality, the implementation of nursing diagnosis based on SDKI is not optimal yet. The purpose of the research is to explore the experiences of nurses in enforcing their nursing diagnosis based on SDKI. Through a qualitative study with a phenomenological approach, using purposive sampling techniques and total of 14 participants. The results of this study led to four themes namely: new challenges, making it easier for nurses, obstacles of SDKI use, form of support for the implementation of SDKI. The result of this study conluded that the use of SDKI makes it easier to the determination of nursing diagnoses. The hospital committee should conduct in-house training on nursing care plans in accordance with the Indonesian Standard of Nursing Diagnosis. Keywords: Experience of Nurse, SDKI, Nursing Diagnosis ABSTRAK Penegakan diagnosis merupakan aspek penting dalam praktik keperawatan. SDKI sebagai pedoman perumusan diagnosis keperawatan telah diberlakukan sejak tahun 2017, akan tetapi pada kenyataannya saat ini penerapan diagnosis keperawatan berdasarkan SDKI belum optimal. Tujuan dari penelitian ini adalah mengeksplorasi pengalaman perawat dalam menegakkan diagnosis keperawatan berdasarkan SDKI, Melalui studi kualitatif dengan pendekatan fenomenologi, menggunakan tehnik purposive sampling dan jumlah 14 partisipan. Hasil penelitian ini memunculkan empat tema yaitu: tantangan baru, memudahkan perawat, kendala penggunaan SDKI, bentuk dukungan penerapan SDKI. Hasil penelitian ini menyimpulkan bahwa Penggunaan SDKI memudahkan dalam penentuan diagnosis keperawatan. Komite rumah sakit perlu melakukan inhouse training tentang nursing care plan yang disesuaikan dengan Standar Diagnosis Keperawatan Indonesia. Kata Kunci: Diagnosis Keperawatan, Pengalaman Perawat, SDKI